Rydberg electromagnetically induced transparency of 85Rb vapor in Ar, Ne, and N2 gases - Bineet Dash; Nithiwadee Thaicharoen; Eric Paradis; Alisher Duspayev; Georg Raithel (APL Quantum)
An experimental study on Rydberg electromagnetically induced transparency (EIT) in rubidium (Rb) vapor cells containing inert gases at pressures ≤5 Torr is reported. Using an inert-gas-free Rb vapor cell as a reference, we measure frequency shift and line broadening of the EIT spectra in Rb vapor cells with argon, neon, or nitrogen gases at pressures ranging from a few mTorr to 5 Torr. The results qualitatively agree with a pseudo-potential model that includes s-wave scattering between the Rydberg electron and the inert-gas atoms and the effect of polarization of the inert-gas atoms by the Rydberg atoms. Our results are important for establishing Rydberg-EIT as an all-optical and non-intrusive spectroscopic probe for field diagnostics in low-pressure radio frequency discharges.